2010
DOI: 10.1002/eji.200940123
|View full text |Cite
|
Sign up to set email alerts
|

The CD4+ T‐cell epitope‐binding register is a critical parameter when generating functional HLA‐DR tetramers with promiscuous peptides

Abstract: Detection of CD4 1 T cells specific for tumor-associated antigens is critical to investigate the spontaneous tumor immunosurveillance and to monitor immunotherapy protocols in patients. We investigated the ability of HLA-DR*1101 multimers to detect CD4 1 T cells specific for three highly promiscuous MAGE-A3 derived peptides: (p39), MAGE-A3 281-295 (p57) and MAGE-A3 286-300 (p58). Tetramers stained specific CD4 1 T cells only when loaded with p39, although all peptides activated the specific T cells when prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Many HLA allelic variants are functionally similar (24-26). As a result, a given epitope may be restricted by multiple HLA molecules encoded by a particular locus (especially if they are close variants), or even molecules from different loci (promiscuous restriction).…”
Section: Resultsmentioning
confidence: 99%
“…Many HLA allelic variants are functionally similar (24-26). As a result, a given epitope may be restricted by multiple HLA molecules encoded by a particular locus (especially if they are close variants), or even molecules from different loci (promiscuous restriction).…”
Section: Resultsmentioning
confidence: 99%
“…This may possibly be associated with lower TCR affinity, and/or different fine specificity. Indeed, it has been shown that a given peptide can make different configurations on a particular MHC class II protein, resulting in different epitopes recognized by different TCR (fine) specificities (43)(44)(45). In this regard, our observations are based solely on a single patient.…”
Section: Discussionmentioning
confidence: 94%
“…There has been considerable interest and progress with respect to initiatives to define and fine‐map peptide epitope/HLA class II interactions in clinical settings 26. We next set out to determine whether the epitopes predicted through HLA transgenic models and predictive algorithms had relevance to T‐cell responses of humans exposed to Bp.…”
Section: Resultsmentioning
confidence: 99%